Tropical Cirrus in Global Storm‐Resolving Models: 1. Role of Deep Convection. Issue 2 (2nd February 2022) - Nugent, J. M.; Turbeville, S. M.; Bretherton, C. S.; Blossey, P. N.; Ackerman, T. P.
Abstract: Pervasive cirrus clouds in the upper troposphere and tropical tropopause layer (TTL) influence the climate by altering the top‐of‐atmosphere radiation balance and stratospheric water vapor budget. These cirrus are often associated with deep convection, which global climate models must parameterize and struggle to accurately simulate. By comparing high‐resolution global storm‐resolving models from the Dynamics of the Atmospheric general circulation Modeled On Non‐hydrostatic Domains (DYAMOND) intercomparison that explicitly simulate deep convection to satellite observations, we assess how well these models simulate deep convection, convectively generated cirrus, and deep convective injection of water into the TTL over representative tropical land and ocean regions. The DYAMOND models simulate deep convective precipitation, organization, and cloud structure fairly well over land and ocean regions, but with clear intermodel differences. All models produce frequent overshooting convection whose strongest updrafts humidify the TTL and are its main source of frozen water. Intermodel differences in cloud properties and convective injection exceed differences between land and ocean regions in each model. We argue that, with further improvements, global storm‐resolving models can better represent tropical cirrus and deep convection in present and future climates than coarser‐resolution climate models. To realize this potential, they must use available observations to perfect their ice microphysics and dynamical flow solvers. Plain Language Summary: High‐altitude tropical cirrus (ice) clouds influence the earth's climate by reflecting sunlight, trapping upwelling radiative energy from the earth's surface, and affecting the temperature and humidity of the upper atmosphere. These clouds are initiated by systems of strong thunderstorms, whose most vigorous updrafts loft water vapor and ice high into the atmosphere. Computer models used to study the global climate struggle to accurately represent tropical thunderstorms because their updrafts are far narrower than the width of a modeled grid cell. Models with very fine grids can better represent the air flows that form these clouds. We investigate how well several fine‐grid models reproduce observed characteristics of tropical thunderstorm systems and cirrus. We find generally good agreement but also substantial differences between individual models, mainly because of their diverse ways of representing ice and snow formation and their evolution. With further observationally motivated improvements, such fine‐grid models should enable more reliable simulations of the role of tropical cirrus in our changing climate. Key Points: Characteristics of tropical cirrus over land and ocean in nine global storm‐resolving models (GSRMs) scatter around observational ranges Most GSRMs reasonably simulate convective organization and rainfall, but with diverse vertical cloud structure through the upper troposphere Deep convection supplies most water to the tropical tropopause layer, with intermodel differences due to updraft speeds and microphysics